COLLISION AND COMPETITION OF FUNDAMENTAL RIGHTS IN GERMAN LAW - Damnjanović, Vojislav (Pravni zapisi, 2018)
Along with vertical effect of fundamental rights, which is undisputable, a more detailed analysis of the bonding-clause from Article 1, Paragraph 3 of the Basic Law for the Federal Republic of Germany has shown that fundamental rights can also develop a horizontal effect. Although in the field of private law the principle of the freedom of contract and autonomy of the will are predominant, in cases of legal dispute, courts are obligated to consider fundamental rights of the parties involved within application of law and in particular when interpreting general clauses. In this respect, in the area of private law it is possible to determine an indirect effect of fundamental rights. Accordingly, fundamental rights which are established by constitution take effect in all areas of law, binding all courts both of ordinary and special jurisdiction, which are obligated to apply them directly. Fundamental rights can collide when two or more legal entities claim their own, most frequently different fundamental rights within the same facts of the case. In addition, there can also be a collision between fundamental rights and other constitutional principles. The problem of Constitutional law collision in German theory and case law is resolved by the principle of practical concordance, which is based on mutual balancing of the colliding interests protected by constitution. In doing so the Federal Constitutional court takes all relevant facts of the individual case into consideration. Contrary to the collision of fundamental rights, the competition of fundamental rights refers to the problem of proper application of the law, when in particular case, several different fundamental rights may be applied. In this regard, the division between freedom rights and equality rights is of major importance. If both freedom rights and equality rights are claimed, the Federal Constitutional court generally undertakes a cumulative examination of the violation of both rights. If violations of fundamental rights of the same group are claimed, certain relations of logical and normative primacy can be established. On the other hand, if there is no relation of primacy between the fundamental rights of the same group, possible violations of the fundamental rights have to be examined cumulatively.